Rwanda : Assessment of the Public Procurement System - World Bank (World Bank, Washington, DC, 2020)
Public procurement of a country is a crucial component of good governance and sustainable economies with inclusive growth and one of the key elements to the effective and efficient functioning of the public sector and service delivery. It underpins the performance of all sectors in public services delivery at different levels of government and thus to the development of the country. Government expenditure on public procurement accounts for a sizeable part of economic activity. Governments around the world spend approximately USD 9.5 trillion in public contracts every year, which could constitute 12-20 percent of a country’s GDP. 1 In Rwanda, the share of government spending as a percentage of gross domestic product (GDP), in 2017, accounts to 15.22 percent2 (Source: The World Bank, TheGlobalEconomy.com). With GDP of USD 9.1 billio